Growth Diagnostics: the case of Palestine - Chiara Marazzi; Gianni Vaggi; Angelica Vitali (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2010)
Growth Diagnostics, GD, by Ricardo Hausmann, Dani Rodrik and Andrés Velasco, represents a useful and practical approach in order to identify the most binding constraints to explain low economic growth. According to the authors the full list of specific economic constraints is unknowable ex-ante, and as a second best solution it is worth trying to identify the feature which represents the major obstacle to the unleashing of the growth potential of a country. This paper has two major aims. In the first part we try to expand the GD method by concentrating on those constraints which appear to be on the 'market/demand side' of the determinants of economic growth, and which widens the 'decision tree' by including a new diagnostic branch represented by Demand-Side variables. This helps to capture the influence of market conditions on profitability and investments. In the second part of the paper we apply the new decision tree to Palestine. The original GD would not allow to identify the most binding constraints to economic growth in Palestine. In fact, Demand-Side elements are fundamental to explain the constraints to Palestinian development. In particular, Palestine suffers from the small dimension of the local markets and from the impossibility to effectively integrate the different markets. Therefore, Palestinian firmsdo not grow and do not reach a size which could make them competitive.
Keywords: O53; O11; E22; 330; Palestine; market size; investment constraints